Improved characterization of heptanes-plus fractions of light crudes (2007)
Heptanes plus fractions have strong effects on the physical properties and phase behaviour of petroleum fluids. It is therefore very important to properly characterize plus fractions. A step to achieving improved characterization is to obtain more realistic molecular weights. Most of the current methods of heptanes plus characterization assume their molecular weights are accurate. However, what is commonly measured in the laboratory is the molecular weight of the complete fluid; the molecular weight of the heptanes plus fraction is then estimated using Kay's mixing rule. Unfortunately, physical properties like molecular weight obtained using 'equivalent fluid' principles by mixing pure components, do not give the same values with actual measurements. Therefore, while a very accurate estimate of the molecular weight of a reservoir oil could be available, that of the heavy fractions, which is 'inferred' could be unreliable, because of the mixing rule. A simple technique has been formulated to achieve improved characterization of petroleum fluids and the heavy fractions. We suggest fine tuning' Kay's mixing rule in order to achieve a match between actual measured molecular weight and the 'equivalent fluid'. Experimental data from over 400 PVT reports from over 100 fields in the Niger Delta were collected and studied A correlation was established between oil gravity and molecular weight and compared with other commonly used correlations. Statistical error analysis was undertaken. Heptanes plus molecular weights which were generally estimated using Kay's mixing rule were found to be generally high and hence fine tuned using a simple technique. The results of this study show that the well-known Cragoe's and Standing correlations gave absolute average deviation of 126.8 and 53.3 respectively for light crudes, compared to 2.5 obtained in this study Furthermore, better description of heavy fractions was achieved with more accurate molecular weight. It is concluded that the proposed technique perhaps provides a theoretical basis for the usual 'tuning' of heptane-plus properties during fluid modelling. It is also concluded that a more accurate correlation for estimating the molecular weight of light crudes has been developed